2004
DOI: 10.1038/nature04165
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal nanocrystal synthesis and the organic–inorganic interface

Abstract: Colloidal nanocrystals are sometimes referred to as 'artificial atoms' because the density of their electronic states-which controls many physical properties-can be widely and easily tuned by adjusting composition, size and shape. The combination of strongly size-and shape-dependent physical properties and ease of fabrication and processing makes nanocrystals promising building blocks for materials with designed functions 1,2 . But the ability to control the uniformity of the size, shape, composition, crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

36
2,767
3
24

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 3,095 publications
(2,830 citation statements)
references
References 65 publications
36
2,767
3
24
Order By: Relevance
“…Although the organic species strongly influence the structural, compositional, and morphological characteristics of the inorganic product and thus offer a versatile tool for tailoring particle size, shape, composition, and surface properties, this is only possible on an empirical basis as long as the organic-inorganic interface is not completely understood on a molecular level and as long as there is no detailed information available about how organic molecules bind and pack on nanocrystal surfaces. 55 …”
Section: Resultsmentioning
confidence: 99%
“…Although the organic species strongly influence the structural, compositional, and morphological characteristics of the inorganic product and thus offer a versatile tool for tailoring particle size, shape, composition, and surface properties, this is only possible on an empirical basis as long as the organic-inorganic interface is not completely understood on a molecular level and as long as there is no detailed information available about how organic molecules bind and pack on nanocrystal surfaces. 55 …”
Section: Resultsmentioning
confidence: 99%
“…The resulting high nucleation and growth rates make "kinetic size focusing" possible, favoring formation of monodisperse nanocrystals. 1,19 Indeed, assynthesized silver nanocrystals have narrow size distributions, as seen in the transmission electron microscopy (TEM) image and the observed particle diameter statistics for a typical sample ( Fig 1A). All the nanocrystals possess an apparently spherical shape and the average diameter is 11.0 ± 1.1 nm.…”
mentioning
confidence: 87%
“…1,2 The literature now contains several cases with chemical transformations being accompanied by varying degrees of modification of properties, including crystal structure and particle shape. [3][4][5] As a recent example, we demonstrated that as-synthesized metallic nanocrystals yield, upon oxidation, nanostructures with modified morphologies such as hollow particles.…”
mentioning
confidence: 99%
“…Starting with preparations of simple objects like spherical nanoparticles [1,2], the field is now moving toward more and more sophisticated structures where size, shape and connectivity of multiple parts of a multicomponent structure can be tailored in an independent and predictable manner [3,4]. Traditional molecular chemistry has proven that synthetic methodology should rely on a toolbox of robust and reproducible techniques.…”
mentioning
confidence: 99%